The Implication of Chemotypic Variation on the Anti-Oxidant and Anti-Cancer Activities of Sutherlandia frutescens (L.) R.Br. (Fabaceae) from Different Geographic Locations - Samkele Zonyane; Olaniyi A. Fawole; Chris la Grange; Maria A. Stander; Umezuruike L. Opara; Nokwanda P. Makunga (MDPI AG, 2020)
Extracts of Sutherlandia frutescens (cancer bush) exhibit considerable qualitative and quantitative chemical variability depending on their natural wild origins. The purpose of this study was thus to determine bioactivity of extracts from different regions using in vitro antioxidant and anti-cancer assays. Extracts of the species are complex and are predominantly composed of a species-specific set of triterpene saponins (cycloartanol glycosides), the sutherlandiosides, and flavonoids (quercetin and kaempferol glycosides), the sutherlandins. For the Folin-Ciocalteu phenolics test values of 93.311 to 125.330 mg GAE/g DE were obtained. The flavonoids ranged from 54.831 to 66.073 mg CE/g DE using the aluminum chloride assay. Extracts from different sites were also assayed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH•) radical scavenging method and ferric reducing anti-oxidant power (FRAP) methods. This was followed by an in vitro Cell Titer-Glo viability assay of various ecotypes using the DLD-1 colon cancer cell line. All test extracts displayed anti-oxidant activity through the DPPH• radical scavenging mechanism, with IC50 values ranging from 3.171 to 7.707 µg·mL−1. However, the degree of anti-oxidant effects differed on a chemotypic basis with coastal plants from Gansbaai and Pearly Beach (Western Cape) exhibiting superior activity whereas the Victoria West inland group from the Northern Cape, consistently showed the weakest anti-oxidant activity for both the DPPH• and FRAP methods. All extracts showed cytotoxicity on DLD-1 colon cancer cells at the test concentration of 200 µg·mL−1 but Sutherlandia plants from Colesburg (Northern Cape) exhibited the highest anti-cancer activity. These findings confirm that S. frutescens specimens display variability in their bioactive capacities based on their natural location, illustrating the importance of choosing relevant ecotypes for medicinal purposes.